Memorial March 1776-1876 - E. Mack::::::::: (Oliver Ditson & Co.)
Piano score, 8 p. c1875 by Lee & Walker. Cover lithograph of the Fine Arts Building by T. Sinclair & Son, Philadelphia. Publishers advertisement on verso of last leaf.